1976
DOI: 10.1073/pnas.73.12.4415
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of 3-phosphohistidine from phosphorylated pyruvate, phosphate dikinase.

Abstract: (3,4) have demonstrated that the pyruvate,phosphate dikinase reaction occurs by a three-site nonclassical Tri (Uni Uni) Ping Pong mechanism. A pyrophosphoryl-and phosphoryl-histidyl residue of the enzyme has been proposed to serve as a carrier between the three sites (4).A number of enzymes that have reaction mechanisms involving phosphate moieties covalently bound to enzyme are now known (5). The phosphate has been found linked to proteins through different types of linkage, including a phosphoester with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0

Year Published

1977
1977
2002
2002

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 30 publications
3
27
0
Order By: Relevance
“…3 The mechanism of the phosphotransfer reaction in pyruvate phosphate dikinase involves the reversible phosphorylation of a histidine residue. 18,19 In this enzyme, the binding sites of the nucleotide and the pyruvate are in distant locations on the protein, and the shuttling of the phosphorylated histidine residue between the two active sites is accomplished by a dramatic swivel of the phospho-histidine domain. 20 Inspection of the multiple alignment of inositol 1,3,4-trisphosphate 5/6-kinase sequences has indicated that this kinase also belongs to the ATP-grasp family.…”
Section: Classification Of Kinasesmentioning
confidence: 99%
See 1 more Smart Citation
“…3 The mechanism of the phosphotransfer reaction in pyruvate phosphate dikinase involves the reversible phosphorylation of a histidine residue. 18,19 In this enzyme, the binding sites of the nucleotide and the pyruvate are in distant locations on the protein, and the shuttling of the phosphorylated histidine residue between the two active sites is accomplished by a dramatic swivel of the phospho-histidine domain. 20 Inspection of the multiple alignment of inositol 1,3,4-trisphosphate 5/6-kinase sequences has indicated that this kinase also belongs to the ATP-grasp family.…”
Section: Classification Of Kinasesmentioning
confidence: 99%
“…18,19 Although the mechanism utilized by protein kinases is currently a matter of debate, the phosphotransfer reaction in this family is thought to proceed either via a proposed simultaneous transfer mechanism, 15 which falls into the category of transition-state stabilization, or via acid -base catalysis. A second example includes the families of the ferredoxin-like fold group.…”
Section: Metal Binding and Catalysismentioning
confidence: 99%
“…The crude yellow product was chromatographed on 350 g of silica gel and eluted with ether-hexane (1:l): 'H NMR (400 MHz, CDC13-TMS) 6 The mixture was stirred 30 min and then a solution of CHJ (1.53 g, 10.77 mmol) in 5 mL of THF was added.…”
Section: L-methoxy-l-phenylmethyl)-4-methylthiazole (4g)mentioning
confidence: 99%
“…The resulting thick slurry was washed several times with anhydrous ether until compound lg, 0.6 g (81%), precipitated as a white powder: 'H NMR (200 MHz, Me2SO-TMS): 6 9.45. To a solution of compound 4g (0.5 g, 2.3 mmol) in 20 mL of anhydrous CH2C12 at 0 OC, was added (CH,)30BF4 (0.34 g, 2.3 mmol) in one portion.…”
Section: 1-methoxy-l-phenylmethyl)-n4-dimethylthiazolium Fluoroboratementioning
confidence: 99%
See 1 more Smart Citation